2010
DOI: 10.1186/1758-2555-2-13
|View full text |Cite
|
Sign up to set email alerts
|

The differential effects of core stabilization exercise regime and conventional physiotherapy regime on postural control parameters during perturbation in patients with movement and control impairment chronic low back pain

Abstract: BackgroundThe purpose of the present study was to examine the differential effect of core stability exercise training and conventional physiotherapy regime on altered postural control parameters in patients with chronic low back pain (CLBP). As heterogeneity in CLBP population moderates the effect of intervention on outcomes, in this study, interventions approaches were used based on sub-groups of CLBP.MethodsThis was an allocation concealed, blinded, sequential and pragmatic control trial. Three groups of par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
23
1
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(34 citation statements)
references
References 42 publications
4
23
1
5
Order By: Relevance
“…The COP sway analysis showed that the COP AP and COP ML sway velocities, SDs, and areas were improved markedly after the ADIM training. This finding corroborates the observations of other recent authors 7,8 who investigated the effect of core-stabilization exercises on bipedal postural stability. Muthukrishnan et al 8 compared the long-term effects of core-stabilization exercise (progression from static to dynamic) and conventional physical therapy in patients with chronic LBP and found improvements in the dynamic postural-stability measures (force, moment, and COP) that were comparable with those of healthy controls.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The COP sway analysis showed that the COP AP and COP ML sway velocities, SDs, and areas were improved markedly after the ADIM training. This finding corroborates the observations of other recent authors 7,8 who investigated the effect of core-stabilization exercises on bipedal postural stability. Muthukrishnan et al 8 compared the long-term effects of core-stabilization exercise (progression from static to dynamic) and conventional physical therapy in patients with chronic LBP and found improvements in the dynamic postural-stability measures (force, moment, and COP) that were comparable with those of healthy controls.…”
Section: Discussionsupporting
confidence: 83%
“…5 Similarly, Kaji et al 7 evaluated the immediate effect of core-stabilization exercise on static bipedal postural sway in 17 healthy young adults and showed a reduction in the COP sway area and velocity in the mediolateral direction. Muthukrishnan et al 8 compared the differential effects of core-stabilization exercise (static and dynamic) and conventional physiotherapy (mobilization, manipulation, traction, interferential therapy, hyperextension exercise, isometric trunk lifts, pelvic tilts, and basic strengthening exercises) on bipedal postural stability in individuals with LBP and compared their stability measures with those of normal controls. Whereas the core-stabilization exercise resulted in improved postural stability, the conventional physiotherapy did not reveal any meaningful changes, suggesting the important role of the former.…”
mentioning
confidence: 99%
“…The timing between trunk and pelvic rotations and erector spinae activity varies systematically with walking velocity and any alteration is reflected in spinal stabilization during unexpec ted perturbations (Lamoth et al 2007). Lumbar stabilization exercises causes significant improvements in disability scores and ground reaction forces, due to improved changes in load transfer patterns during perturbation (Muthukrishnan et al 2010). Phasic superficial paraspinal activity is associated with foot strike which controls trunk motion in the frontal and sagittal planes during locomotion.…”
Section: Discussionmentioning
confidence: 99%
“…However, core stability exercise demonstrates significant improvements in: distribution of ground reaction forces, use of optimized postural adjustments in the direction of perturbation, 20% absolute risk reduction of flare-up during intervention and 40% absolute risk reduction for resolution of back pain after core instability exercises (Muthukrishnan et al, 2010).…”
Section: Studies Comparing Stability Programs and Othersmentioning
confidence: 99%
“…These studies have addressed the need of homogenous chronic low back pain group for better clinical outcomes. Evaluating postural control parameters such as centre of pressure displacements, moments and forces following interventions, particularly stability exercises, may provide insight into how this surrogate outcomes are mediated by different subgroups or heterogeneous chronic low back pain patients and identifying subgroups of chronic low back pain patients who are most likely to benefit after particular intervention (Muthukrishnan et al, 2010).…”
Section: Studies Comparing Stability Programs and Othersmentioning
confidence: 99%